2021
DOI: 10.1111/ijcp.13950
|View full text |Cite
|
Sign up to set email alerts
|

The stone crescent of Anatolia

Abstract: Objectives To assess the largest stone composition data available and to present the variations in the stone composition according to gender and different climatic environments in Turkey. Methodology Data for a total of 24 768 urinary stone patients from the Turkish Mineral Research and Exploration Institute were evaluated. X‐ray diffraction crystallography was used for analysis and the Köppen‐Trewartha classification was used to assess the climatic features of the cities. After the assessment, the cities were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Inversely, no significant rise in uric acid stones was observed in a study conducted in Italy [24]. Also, in Turkey, calcium oxalate (CaOx) stones have markedly increased from 2006 to 2019 [19]. In addition, there were more uric acid and cystine stones in the Turkish inland areas, which might be because of higher animal protein consumption and more consanguinity marriage in the inland than in other regions across Turkey, as stated by the authors [19].…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…Inversely, no significant rise in uric acid stones was observed in a study conducted in Italy [24]. Also, in Turkey, calcium oxalate (CaOx) stones have markedly increased from 2006 to 2019 [19]. In addition, there were more uric acid and cystine stones in the Turkish inland areas, which might be because of higher animal protein consumption and more consanguinity marriage in the inland than in other regions across Turkey, as stated by the authors [19].…”
Section: Resultsmentioning
confidence: 81%
“…Altai was a leading region in obesity, hypertension, and diabetes prevalence, which can explain the higher frequency of urolithiasis [13 ▪ ]. In Turkey, they found that urolithiasis had a crescent-shape distribution with more stones detected in coastal than inland areas; which can be explained by climate variations as inland had a higher average temperature than other regions [19]. Chen and Chen [15] reported a higher prevalence of urolithiasis in New Brunswick compared with studies conducted in other Canadian provinces.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations